School Policies on the Use of Android Devices in Students Learning Activities during the Covid-19 Pandemic Condition - Nashruddin, Nashruddin; Tanasy, Novalia (Lembaran Ilmu Kependidikan, 2021)
The present study aims at analyzing school policy toward the use of Android devices in the students learning activities during the Covid-19 pandemic condition. The research method used is a qualitative approach with the type of empirical phenomenology research. Six participants were taken using purposive sampling technique as research subjects, consisting of teachers and students’ parents. Data obtained through WhatsApp application. Data was analyzed using empirical phenomenological analysis technique. The results showed that there were 3 aspects analyzed, namely advantages, weaknesses, and expectations of students’ parents towards learning based on Android devices for students. This research concluded that schools should (1) provide opportunities for students to take advantage of Android devices as a learning tool, (2) mediate periodic meetings among teachers and students’ parents to evaluate the behavior and learning outcomes of students, (3) facilitate the learning process so that students and teachers easily access the internet to carry out learning, and (4) guide teachers to improve their digital pedagogy competence to present interesting learning lessons during the Covid-19 pandemic.